Sakamoto days. Vol. 2, Hard-boiled - Suzuki, Yūto (Shonen Jump manga., 2022)
"Taro Sakamoto was once a legendary hit man considered the greatest of all time. Bad guys feared him! Assassins revered him! But then one day he quit, got married, and had a baby. He's now living the quiet life as the owner of a neighborhood store, but how long can Sakamoto enjoy his days of retirement before his past catches up to him?! Shin faces off with a strange assassin who's targeting Mr. Sakamoto, but how will he manage against a foe whose thoughts are unreadable? Then, the Sakamoto gang does their best to enjoy a peaceful family outing at the amusement park, only to be rudely interrupted by a pair of menacing assassins. Can Mr. Sakamoto and his buddies take care of them without his family noticing?"--Amazon.